Burden and Determinants of Severe Anemia among HIV-Infected Adults: Results from a Large Urban HIV Program in Tanzania, East Africa. (March 2015) - Makubi, Abel; Okuma, James; Spiegelman, Donna; Hawkins, Claudia; Darling, Anne Marie; Jackson, Elizabeth; Mugusi, Ferdinand; Chalamilla, Guerino; Fawzi, Wafaie
Background and Methods: This cross-sectional study aimed at determining the prevalence and risk factors for severe anemia, severe microcytic anemia, and severe normocytic anemia among HIV-infected individuals aged >15 years. Univariate and multivariate analyses were performed to identify the risk factors for anemia. Results: Data from 40 408 patients were analyzed, showing an overall prevalence of 22% for severe anemia. The risk of developing severe anemia increased by 49% among patients with a body mass index of <18.5 kg/m 2, by approximately 2-fold among patients with the World Health Organization (WHO) stage III, and by 3-fold among patients with WHO stage IV illness. Severe normocytic anemia was uniquely increased among patients aged ≥50 years, among those with chronic diarrhea and Kaposi's sarcoma, and those taking cotrimoxazole. Conclusion: There was a high prevalence of severe anemia among adults infected with HIV. Focused identification of anemia should be based on the hemoglobin and mean corpuscular volume measurements.